ANALlSIS SUDUT DATANG RADIASI MATAHARI UNTUK PENGEMBANGAN MODEL PINDAH PANAS PADA RUMAH KACA DI DAERAH TROPIKA - Herry Suhardiyanto; Yudi Chadirin; Titin Nuryawati; Yayu Romdhonah (Jurnal Keteknikan Pertanian, 2007)
ABSTRACT A heat transfer model has been developed for a naturally ventilated greenhouse under the tropical climatic conditions. In the tropical region, greenhouses are characterized by high exposure in solar radiation and air exchange through natural ventilation. Therefore in this research, incident angle of solar radiation on the greenhouse roof surface has been considered as an important factor to improve the accuracy in calculating the radiation received by the greenhouse. The heat transfer model consists of four layers represent the cover, inside air, floor surface and soil layers of the greenhouse. The model was applied to a naturally ventilated standard-peak greenhouse. A computer program was developed to predict the temperature of the inside air. Incident angle of direct solar radiation on roof surface and outside microclimate parameters data were used as the input values. Heat transfer equations were solved by using the Runge-Kutta Method while the angle of direct solar radiation with the roof surface was calculated by using the principles of geometry. Results show that the model performed well in predicting the temperature of the inside air as compared to that of the measure value.Diterima:  4 Januari 2007; Disetujui: 26 Pebruari 2007